2019
DOI: 10.1002/rrq.253
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Sourcing in Upper Secondary School: A Comprehensive Sourcing Intervention With Follow‐Up Data

Abstract: In this quasi‐experimental study, the authors examined the effects of an intervention designed to teach upper secondary school students to take source information, such as author expertise, into consideration when selecting, processing, and using textual resources to complete particular multiple‐document literacy tasks. The intervention centered on a contrasting cases approach framed by authentic curriculum‐based classroom activities and was implemented over six weeks by teachers who had participated in profes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 69 publications
0
49
0
1
Order By: Relevance
“…Future research, for instance, could examine the effects of instructional interventions that aim at strengthening Internet-specific beliefs in justification by multiple sources and justification by authority on individuals’ source evaluation and corroboration behaviors during Web search as well as on the learning outcomes associated with such behaviors. Recently, several intervention studies showed that interventions targeting learners’ source evaluation or confronting learners with conflicts across documents can strengthen (a) beliefs in justification by multiple sources (Ferguson et al., 2013; Kammerer et al., 2015) or (b) actual source evaluation and corroboration behaviors or comprehension outcomes (e.g., Bråten, Brante, et al., 2019; McGrew, 2020; for recent reviews, see Brante & Strømsø, 2018; Bråten, Stadtler, et al., 2018; Kammerer & Brand-Gruwel, 2020). However, future studies should examine both epistemic beliefs and behaviors in conjunction as well as their potentially mediational relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Future research, for instance, could examine the effects of instructional interventions that aim at strengthening Internet-specific beliefs in justification by multiple sources and justification by authority on individuals’ source evaluation and corroboration behaviors during Web search as well as on the learning outcomes associated with such behaviors. Recently, several intervention studies showed that interventions targeting learners’ source evaluation or confronting learners with conflicts across documents can strengthen (a) beliefs in justification by multiple sources (Ferguson et al., 2013; Kammerer et al., 2015) or (b) actual source evaluation and corroboration behaviors or comprehension outcomes (e.g., Bråten, Brante, et al., 2019; McGrew, 2020; for recent reviews, see Brante & Strømsø, 2018; Bråten, Stadtler, et al., 2018; Kammerer & Brand-Gruwel, 2020). However, future studies should examine both epistemic beliefs and behaviors in conjunction as well as their potentially mediational relationship.…”
Section: Discussionmentioning
confidence: 99%
“…The number of switches between information units from different texts indicated the degree of content integration. This way of measuring content integration across multiple texts was developed by Britt and Sommer (2004) and has been validated in a number of more recent studies (e.g., Bråten, Brante, & Strømsø, 2019;Bråten et al, 2018a;Gil, Bråten, Vidal-Abarca, & Strømsø, 2010). For example, if a written product contained seven information units altogether, and the first four information units came from one text and the next three information units came from another text, this would count as one switch and indicate poor content integration.…”
Section: Texts Computer Application and Processing And Product Measmentioning
confidence: 99%
“…This strategy may be effective and efficient, but only when proper hints are used and the seeker’s information needs are satisfied in a timely and efficient way (Bromme and Goldman 2014 ; Rieh et al 2016 ). In this sense, a crucial factor for seeking online information successfully is that the information seeker needs to critically reflect on their seeking behavior and sourcing strategies (e.g., Bråten et al 2019 ; Forte 2015 ; Rieh et al 2016 ; Pérez et al 2018 ; second author and first author submitted ). While students in a training on sourcing online information did initially use and check for information about the trustworthiness of the provider of information, they did not critically reflect on what they found from the trustworthiness check (Brante 2019 ).…”
Section: The Role Of Trust When Sourcing Online Informationmentioning
confidence: 99%
“…While students in a training on sourcing online information did initially use and check for information about the trustworthiness of the provider of information, they did not critically reflect on what they found from the trustworthiness check (Brante 2019 ). However, in educational interventions that encouraged students to not only identify and assess trustworthiness criteria but also critically reflect on the sourcing of information, students more elaborately integrated information about the perceived trustworthiness of the provider (Bråten et al 2019 ; Pérez et al 2018 ).…”
Section: The Role Of Trust When Sourcing Online Informationmentioning
confidence: 99%
See 1 more Smart Citation